Prevalence and Patterns of self-medication practices in the urban areas of Belagavi, Karnataka; A Community Based Study - A Bellad, Asha; George, Gibin (Indian Journal of Community Health, 2025)
Background: Self-medication, the use of drugs without professional supervision for self-diagnosed ailments, is a global public health concern. In India, high prevalence stems from easy OTC drug access, economic constraints, and limited healthcare services. The WHO highlights the need to understand self-medication to address risks like adverse drug reactions and antimicrobial resistance. Aim & Objective: To evaluate the prevalence and patterns of self-medication practices among the urban population of Belagavi, Karnataka. Methods and Material: A community-based cross-sectional study was conducted from October 2022 to September 2023, involving 400 systematically selected participants from two urban health centres. Data was collected through face-to-face interviews using a validated questionnaire and analysed using SPSS 25.0 with descriptive statistics. Results: The study found that 62.3% of participants practiced self-medication in the last three months. The sample included 51.8% females and 48.2% males, with the highest prevalence in the 21–30 age group (24.0%). Most were married (80.5%) and graduates (26.5%). Key reasons were time-saving (54.5%) and previous prescriptions (24.3%). Common symptoms were headache (79.5%) and fever (47.8%), with paracetamol (98%) being the most used medication. Conclusions: The high prevalence of self-medication in urban Belagavi underscores the urgent need for targeted public health interventions. We recommend measures to improve healthcare accessibility, implement stricter regulations for over-the-counter medications, and promote health education as a crucial tool to foster responsible medication use and mitigate potential health risks, which can be severe and life-threatening.